Pengaruh Quality Of Work Life Terhadap Kinerja Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada Guru Dan Karyawan Smk Terpadu Al-Ishlahiyah Singosari - Nofan Adi Saputra; Abdul Kodir Djaelani; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to determine the effect of Quality of Work Life on Performance through Job Satisfaction as an Intervening Variable in Teachers and Employees of Integrated Al-Ishlahiyah Singosari. The data used in this study uses primary data by distributing questionnaires to respondents. The study population was teachers and employees of Al-Ishlahiyah Singosari Integrated Vocational School, while the sample in this study were 46 respondents. The analytical method used in this study is path analysis, single test with hypothesis testing using the t test. From this study, the results show that there is an influence between Quality of Work Life on Performance through Job Satisfaction as an Intervening Variable Keywords: Quality of Work Life, Job Satisfaction, and Performance